The Impact of Covid-19 Pandemic on Students’ Sedentary Behavior in Indonesia - Syiva Fitria (Universitas Serambi Mekkah, 2021)
Indonesia is one among many countries applies lockdown or large-scale socialrestriction in order to suppress transmission rates. The current study examines theimpact of COVID-19 pandemic lockdown decision on sedentary behavior amongadolescents in Indonesia. An online survey was administered to 255 adolescentson August until October. The online survey consists of questions on demographicinformation and Adolescence Sedentary Activity Questionnaire (ASAQ).Statistical analysis was performed to compare the difference between total hoursspend on performing sedentary behavior before and after the pandemic. A pairedsample t-test revealed there was a significant difference in total hours spend onperforming sedentary behavior before and after the pandemic (t (254) = -12.8,p<.001). Adolescence is performing more sedentary behavior after the pandemic(M=10.43, SD=3.11) compared to the time before the pandemic (M=8.68,SD=3.47). In conclusion, the covid-19 pandemic cause change on sedentarybehavior where there were increase of the total hour adolescence spend onperforming sedentary behavior, including a significant change in learningbehavior.